Analisis Potensi Budaya Lokal sebagai Atraksi Wisata Dusun Segunung - Rahmatin, Leily (Jurnal Kajian dan Terapan Pariwisata, 2023)
Cultural potential as a tourist attraction is considered one of the biggest factors in attracting tourists. Pioneered tourism destinations that carry local wisdom are potential superior tourist attractions. Various tourism potentials are interesting to develop but are also expected to become sustainable as a form of sustainability of tourism activities currently being developed. The suitability of the goals of developing cultural tourism with the implementation of tourism development management is an important aspect to analyze, so that the development of tourism potential can also become a vessel for preserving local culture. The importance of this paper as a form of analysis of local culture-based tourism potential which can become a tourist attraction that can provide tourism competitiveness value but also pays attention to the value of authenticity found in the Segunung Traditional Village. The research method used is descriptive qualitative with data collection techniques in the form of direct observation and in-depth interviews. The tourism potential which is an opportunity for the development of Segunung Traditional Village Tourism, most aspects of tourism products contained in tourism destinations are tourist attractions with a cultural concept. The aim of cultural tourism is to promote understanding, appreciation preservation of various cultures so that existing local wisdom can be maintained and useful in increasing the welfare of local communities through tourism.